Self-Development by Exploring The Talent Interests of Students of SMK Neg.2 Medan - Dina Maizana; Irwansyah Putra; Nurmaida Irawani Siregar (CV. AFDIFAL MAJU BERKAH, 2023)
When choosing a major, school students need to know their interests and talents. Choosing the right major will provide maximum learning development. So that students are able to master the curriculum provided based on the major they are following. And a student in the future can work in the field of his interest according to his abilities, interests and talents. It is also important for the future of students to explore knowledge skills